IDENTIFICATION OF WEATHERING ROCK IN EVOLUTION OF ACID MINE DRAINAGE FORMING ON LABORATORY-SCALE KINETIC TEST USING GEOCHEMICAL-MINERALOGY-TEXTURE APPROACH: CASE STUDY OF HIGH SULPHIDATION EPITHERMAL DEPOSITS - Syaputra, Rizky
Weathering of rocks has an important role in forming Acid Mine Drainage/Acid Rock Drainage (AMD/ARD), which is one of the main environmental problems. AMD arises due to the oxidation of sulfide minerals when interacting with air and moisture. This study focuses on the interaction between physical and chemical weathering of rocks and their effect on the formation of AMD. This study aimed to determine changes in mineralogy and rock texture parameters during laboratoryscale kinetic column testing using a geochemical-mineralogy-texture (GMT) approach. A total of eight rock samples were used consisting of different geological domains from a high sulphidation epithermal (HSE) gold mine in North Sulawesi, Indonesia. The kinetic test column was carried out for 160 to 180 days with flushing cycle intervals of one day, three days, and one week.